Pedagogical Providing of Beginning of Intellectual Culture of the Juniors Taking into Account Their Intellectual and Psychological Sex - Solovyova, Tatiana; Shiryaykina, Olesya (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article is devoted pedagogical support formation of cognitive-evaluative, instrumental, motivational and volitional, emotional and creative components of the intellectual culture among the juniors in educational process, taking into account whether they are masculine or feminine intellectual and psychological sex.